1995
DOI: 10.1063/1.868767
|View full text |Cite
|
Sign up to set email alerts
|

A consistent hydrodynamic boundary condition for the lattice Boltzmann method

Abstract: A hydrodynamic boundary condition is developed to replace the heuristic bounce-back boundary condition used in the majority of lattice Boltzmann simulations. This boundary condition is applied to the two-dimensional, steady flow of an incompressible fluid between two parallel plates. Poiseuille flow with stationary plates, and a constant pressure gradient is simulated to machine accuracy over the full range of relaxation times and pressure gradients. A second problem involves a moving upper plate and the injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(161 citation statements)
references
References 15 publications
0
156
0
3
Order By: Relevance
“…2 shows the incoming distribution functions as dashed lines and the full lines represent the known functions. Bennett [16] argued that, similar in spirit to Noble et al [17], we can calculate the unknown distribution functions purely from constraints imposed on the hydrodynamic moments at the boundary. The basic idea of this method is summarised as follows.…”
Section: Moment-based Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows the incoming distribution functions as dashed lines and the full lines represent the known functions. Bennett [16] argued that, similar in spirit to Noble et al [17], we can calculate the unknown distribution functions purely from constraints imposed on the hydrodynamic moments at the boundary. The basic idea of this method is summarised as follows.…”
Section: Moment-based Boundary Conditionsmentioning
confidence: 99%
“…The presented boundary conditions, the so-called "Moment Method", are another way to impose conditions directly upon the moments of the LBM [16]. The momentbased implementation discussed here uses only hydrodynamic moments to satisfy boundary conditions and may be viewed as a direct extension of the method first proposed by Noble et al [17] for simpler lattices. The moment method has already been applied to diffusive slip [18], natural convection problems [19], the slipflow regime [20], and wetting phenomena in multiphase flow [21], and reported very favourable results.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the BBL scheme gives second-order accurate result for straight walls [33,19]. Noble et al developed a second-order accurate boundary condition to compute f s but it is only applicable to straight walls in triangular lattice space [27]. He et al generalized the scheme of Noble et al to arbitrary lattice [19].…”
Section: (Xi + E a Andu T + St)-f A (Xi T) = --[F A (X It T) -F A Eq) mentioning
confidence: 99%
“…Some of these more sophisticated solid-fluid boundaries are restricted to regular geometries [28,29], but there are also general boundary-fitted models [30,31] available. For practical simulations the bounce-back boundary is however very attractive, because it is a simple and computationally efficient method for imposing no-flow conditions on irregularly shaped walls.…”
Section: Boundary Conditionsmentioning
confidence: 99%